Biological Characterization of Cleome felina L.f. Extracts for Phytochemical, Antimicrobial, and Hepatoprotective Activities in Wister Albino Rats - Heena Yaqub Shaikh; Shaik Kalimulla Niazi; Asmatanzeem Bepari; Mary Anne Wong Cordero; Shazima Sheereen; Syed Arif Hussain; Muthuraj Rudrappa; Shashiraj Kariyellappa Nagaraja; Shekappa Ningappa Agadi (MDPI AG, 2023)
The present study aims to explore the phytochemical constitution and biological activities of Cleome felina L.f. (Cleomaceae). C. felina (leaves, stem, and root) extracts (acetone, methanol, and water) were qualitatively assessed for phytochemical presence. Methanolic leaves extract revealed more positive phyto-compounds among all the extracts; further, methanolic leaves extract was evaluated for FTIR, EDX, GCMS, antimicrobial assay, acute toxicity, and paracetamol-induced hepatoprotective activity in Wister albino rats. FTIR and EDX analysis unveiled important functional groups and elements in the leaves. GCMS analysis of methanolic leaves extract exposed 12 active phyto-compounds: major constituents detected were 1-Butanol, 3-methyl-, formate-48.79%; 1-Decanol, 2-ethyl-13.40%; 1,6-Anhydro-β-d-talopyranose-12.49%; Ethene, 1,2-bis(methylthio)-7.22%; Decane-4.02%; 3-Methylene-7, 11-dimethyl-1-dodecene-3.085%; Amlexanox-2.50%; 1,2,3,4-Cyclopentanetetrol, (1α,2β,3β,4α)-2.07%; L-Cysteine S-sulfate-1.84%; n-Hexadecanoic acid-1.70%; and Flucarbazone-1.55%. The antimicrobial assay showed a moderate zone of inhibition against S. aureus, B. cereus, E. coli, P. aeruginosa, C. albicans, and C. glabrata at 100 µL/mL concentration. Additionally, acute toxicity revealed no behavioral sign of the toxic effect. The significant results were obtained for methanolic leaves extract (low-50 and high-100 mg/kg b.wt. dose) for hepatoprotective activity, where it dramatically reduced serum blood biochemical markers (AST, ALT, ALP, Total bilirubin, and cholesterol) and exhibited elevated hepatic antioxidant enzymes (SOD, CAT, and GSH) concentration with lipid peroxidation retardation. To conclude, C. felina methanolic leaves extract ameliorated important phytochemical compounds and showed significant antimicrobial and hepatoprotective efficacy; therefore, utilization of C. felina leaves suggested in pharmacological applications, and in numerous cosmetics, herbicides, and food industries, would be a great scope for future hepatoprotective drug designing.